Evaluation of some Biochemical and Hematological Parameters in Patients with Chronic Kidney Disease - AlAni, Hadeel T.; Al-Lami, Makarim Q. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Chronic kidney disease is a condition that results from an indefinite change in the structure and function of the kidneys. A slow, steady progression characterizes it and is irreversible. Objectives: This study aims to evaluate the findings of certain biochemical and hematological tests in samples from Iraqi CKD patients. Methods: This study included 90 subjects, where 70 patients with chronic kidney disease and 20 healthy individuals. Blood samples were collected from the patients during their visits to Ghazi Al-Hariri Surgical Specialties’ Hospital- Medical City, Baghdad, Iraq. Age, sex and body mass index were assessed for each participant followed by renal function tests [serum blood urea, creatinine, uric acid and estimated glomerular filtration rate], and complete blood count. Also, serum levels of uromodulin and cystatin C were measured statistically studies were carried out using analysis of variance (ANOVA). Results: the study demonstrated a highly significant (P<0.001) increase in blood urea, serum creatinine and uric acid levels, while a significant (P<0.05) decrease in estimated glomerular filtration rate levels in patients compared to the control group. On the other hand, it showed a highly significant (P<0.001) decrease in hemoglobin and hematocrit values and a significant (P<0.05) decrease in the red blood cell count. Patients had revealed a significant (P<0.05) increase in cystatin C level and a decrease in uromodulin level when compared to the control group. conclusion: the present study shows that chronic kidney disease patients have upregulated renal function parameters blood urea, serum creatinine and with downregulated estimated glomerular filtration rate, while hematological disorder was more prevalent in patients. On the other hand, cystatin C level revealed an increase while uromodulin level showed a decrease in Iraqi patients.